Workload and Psychological Well‑Being Among Nurses Pursuing Higher Education: A Descriptive Quantitative Study (Journal of Islamic Nursing, 2026)
Abstract   Nurses undergoing study leave face dual roles responsibilities as healthcare providers in clinical settings and as students pursuing professional advancement. This dual role may lead to increased workload and mental health challenges. The purpose of this study was to describe the workload and mental status of nurses undergoing study leave. A descriptive cross-sectional design was applied. The accessible population comprised 73 nurses enrolled in the Nursing Professional Program, and 57 were selected through purposive sampling. Inclusion criteria were students of the Nursing Professional Program who work as nurses in health facilities and are undergoing study leave, and willing to participate. Data were collected using two standardized instruments: NASA‑TLX to assess workload and DASS‑21 to evaluate depression, anxiety, and stress. Questionnaires were analyzed univariately. The workload was perceived by respondents most dominantly in the very high category (52%), with the dominant factor causing the workload being the Temporal Demand (TD). The most dominant mental status was in the normal category for depression (89%), anxiety (67%), and stress (86%). However, some respondents experienced mild to moderate depression, mild to severe anxiety, and moderate to mild stress. Nurses undergoing study leave experience substantial time pressure in balancing clinical and academic responsibilities, which may increase fatigue and reduce cognitive resources. Despite most respondents remaining in the normal range for depression, anxiety, and stress, the presence of mild to moderate symptoms highlights the need for workload management, early mental‑health monitoring, and coordinated hospital–university policies that recognize and support the dual role of these nurses.   Keywords: Clinical practice, Mental Status, Nurses, Nursing Students, Study Leave, Workload